A long-term analysis of pumped hydro storage to firm wind power. (1st January 2015) - Foley, A.M.; Leahy, P.G.; Li, K.; McKeogh, E.J.; Morrison, A.P.
Highlights: This is a long term generation analysis of a high wind power system. A high CO2 & fossil fuel price is closest to Ireland's EU ETS 2020 target. New pumped storage to firm wind is limited unless strong market costs exist. Reserve for wind power show that ancillary services are relevant for balancing. Abstract: Although pumped hydro storage is seen as a strategic key asset by grid operators, financing it is complicated in new liberalised markets. It could be argued that the optimum generation portfolio is now determined by the economic viability of generators based on a short to medium term return on investment. This has meant that capital intensive projects such as pumped hydro storage are less attractive for wholesale electricity companies because the payback periods are too long. In tandem a significant amount of wind power has entered the generation mix, which has resulted in operating and planning integration issues due to wind's inherent uncertain, varying spatial and temporal nature. These integration issues can be overcome using fast acting gas peaking plant or energy storage. Most analysis of wind power integration using storage to date has used stochastic optimisation for power system balancing or arbitrage modelling to examine techno-economic viability. In this research a deterministic dynamic programming long term generation expansion model is employed to optimise the generation mix, total system costs and total carbon dioxide emissions, and unlike other studies calculates reserve to firm wind power. The key finding of this study is that the incentive to build capital-intensive pumped hydro storage to firm wind power is limited unless exogenous market costs come very strongly into play. Furthermore it was demonstrated that reserve increases with increasing wind power showing the importance of ancillary services in future power systems.